Cyclical stabilisation under the stability and growth pact: How effective are automatic stabilisers? - Anne Brunila; Marco Buti; Jan in't Veld (Bank of Finland, 2002)
It is widely recognised that fiscal policy will have greater responsibilities for cyclical stabilisation in the EMU, given the loss of the monetary instrument at national level.At the same time, the EMU's budgetary framework emphasises the need to rely on automatic fiscal stabilisers, rather than active policies, in cushioning the business cycle.We show that automatic stabilisers are relatively powerful in the event of a shock to private consumption, but less so as regards shocks to private investment and exports.In respect of supply side shocks, automatic stabilisers are largely ineffective, which may in fact be a good thing to the extent that supply-side disturbances call for structural adjustment rather than cyclical stabilisation.Looking ahead, one of the challenges facing policy-makers will be how to design tax and welfare reforms which, while improving incentives and market functioning, do not stifle - and in fact could strengthen - the impact of automatic stabilisers.
URN:NBN:fi:bof-20140807211
Keywords: 330; cyclical stabilisation; automatic stabilisers; Stability and Growth Pact